Don't need help, don't want help, can't get help: How patients with brain tumors account for not using rehabilitation, psychosocial and community services. Issue 9 (September 2017) - Langbecker, Danette; Ekberg, Stuart; Yates, Patsy
Highlights: Patients may downplay or not recognize their issues or problems. Patients may not understand if their issues are 'normal' or can be treated. Patients may wish to self-manage or use informal sources of support. Patients' limitations may themselves act as barriers to accessing services. Abstract: Objective: To understand why some adults with primary brain tumors do not use support services despite indications of a need for help. Methods: Nineteen adults recently diagnosed with primary brain tumors participated in semi-structured interviews. Thematic analysis was used to identify recurrent ways participants explained their non-use of support services. Results: Some patients indicated that they did not use support services as they did not need help, in particular reporting positive experiences relative to their expectations or to others, that their needs were met, or difficulties recognizing their needs. Some patients reported not wanting help, citing preferences to self-manage, other priorities, or negative perceptions of the services available. Many patients identified barriers to support service utilization, particularly problems recognizing that services could address their needs and that their needs were valid concerns. Conclusion: The gap between patients' needs and their service use may result from patients' expectations from the medical system, shifting of standards for well-being, cognitive changes, and access issues. Practice implications: Addressing knowledge barriers and perceptions relating to help-seeking, as well as recognizing the challenges specific to this patient group in terms of need recognition and access issues, may assist in improving patients' physical, psychological and social well-being.